Interfacial analysis of carbon nanotubes-reinforced and graphene-reinforced Sn-1.0Ag-0.5Cu solder on electroless nickel/ immersion silver surface finish - Krishna, Vidyatharran (2020)
Interconnection material examination of composite solder materials and general comparison of the joints with the solder alloy are fundamental to search for more comparable and dependable alternative to the solder candidate. In this investigation, SAC105 carries two reinforced parameters, carbon nanotubes (CNTs) and graphene nanosheets (GNS), alongside with two different surface finish, electroless nickel/ immersion silver (ENImAg) and copper substrate. This is because the plain SAC105 facing extreme deterioration of IMC formation and weak mechanical strength compared with reinforced SAC105. Thus, evaluation of the intermetallic compound formation and shear strength properties of ENImAg-based Sn-1.0Ag-0.5Cu solder were carried with the addition of carbon nanotubes reinforced solder systems (Sn-1Ag-0.5Cu-xCNT; x = 0.01, 0.05, and 0.1 wt%), and graphene nanosheets reinforced solder systems (Sn-1Ag-0.5Cu-xGNS; x = 0.01, 0.05, and 0.1 wt%), which were completely mixed over the powder metallurgy process. Reflow on the electroless nickel/immersion silver (ENImAg) and copper surface finish were carried at an optimum temperature of 260°C, to analyze the characterization of the intermetallic compound growth and solder joint microstructure among the plain and composite solders with multi surface finishes. By the same token, a single-lap solder joint system was experimented to assess the shear strength of all the solder samples using similar reflow temperature used for the solder joint characterization. In general, the GNSs and CNTs increased the melting point. The highest melting temperatures received from the DSC scan are 233.44°C for 0.1GNSs composite solder and 232.27°C for 0.1CNTs composite solder. Besides that, the wetting angle shown by GNS-based solders reduced more than CNT-based solders. From the IMC thickness result obtained, a slight change within the total intermetallic compound layer growth was detected in the solder joints, where the thinnest IMC thicknesses are 3.35 μm and 2.53 μm recorded for the SAC105-0.1GNS with copper board and SAC105-0.1GNS with ENImAg board respectively among the overall solders compositions, whereas the 0.01CNT-base solders shows the thinnest between the other CNT compositions, which is 3.61 μm and 2.65 μm for Cu substrate and ENImAg substrate individually. On the contrary, the shear strength properties shown by SAC105-0.01GNS is the best among the rest of the single-lap solder joints board, which is 11.2MPa for Cu-based substrate and 12.11MPa for ENImAg-based substrate. As conclusion, adding the reinforcements to the plain solder improved the wettability, microstructural growth and shear properties, especially with GNS reinforcement samples. Meanwhile, ENImAg surface finish improve the reliability of the solders more than Cu surface finish.